An Overview of the Self-Concept of Out-of-Region Students on Guidance and Counseling Study Program - Richasary, Amalia; Kurniasari, Rizma; Permana, Dwiky Janget; Sari, Widya Juwita (IKIP Siliwangi, 2024)
English: The phenomenon of educational equity has facilitated educational mobility across regional boundaries, it makes many students choosing to study at educational institutions in other regions. However, this experience is often followed by unique psychological challenges. Self-concept plays a role in determining an individual's mental/psychological development. Self-concept is also a better predictor of future-oriented motivation for career aspirations in science. This study aims to explain the description of the self-concept of overseas students in the Guidance and Counseling Study Program at Yogyakarta State University. The research design used in this study is to use descriptive quantitative methods. The variable is self-concept. The subjects of this study were active students who were overseas students in the Guidance and Counseling Study Program of FIPP UNY. The data collection instrument used the Tennessee Self Concept Scale (TSCS) translated by Sri Rahayu Partosuwido, et al. The scale that has been translated are valid and reliable. Indonesia: Fenomena pemerataan pendidikan telah memfasilitasi mobilitas pendidikan lintas batas daerah, yang menyebabkan semakin banyak mahasiswa memilih untuk belajar di institusi pendidikan di daerah lain. Namun, pengalaman ini seringkali diikuti oleh tantangan psikologis yang unik. Konsep diri memiliki peran penting dalam menentukan perkembangan mental/psikologis individu. Konsep diri juga merupakan prediktor yang lebih baik dari motivasi yang berorientasi masa depan untuk cita-cita karir dalam ilmu. Penelitian ini bertujuan untuk menjelaskan gambaran konsep diri mahasiswa perantauan di Prodi Bimbingan dan Konseling Universitas Negeri Yogyakarta. Rancangan penelitian yang digunakan penelitian ini adalah dengan menggunakan metode kuantitatif deskriptif. Variabel dalam penelitian ini adalah konsep diri. Subjek dari penelitian ini merupakan mahasiswa aktif yang merupakan mahasiswa perantauan di Prodi BK FIPP UNY. Instrumen pengumpulan data menggunakan skala Tennessee Self Concept Scale (TSCS) terjemahan Sri Rahayu Partosuwido, dkk. yang telah dilakukan oleh sri rahayu Partosuwindo, dkk, skala yang telah diterjemahkan semua butir item valid dan reliabel.